2008
DOI: 10.1177/0017896908089390
|View full text |Cite
|
Sign up to set email alerts
|

Food hygiene education in UK secondary schools: A nationwide survey of teachers' views

Abstract: Objective A nationwide survey of teachers investigated the teaching of food hygiene in UK secondary schools. Previous studies have focused on effective strategies in consumer food hygiene training but there is little research focusing on school-based education. Design The questionnaire was developed based on the results of in-depth interviews with school teachers and included topics such as where teachers gained up-to-date food hygiene knowledge and how key food hygiene messages were reinforced. Setting Postal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 15 publications
(18 reference statements)
0
16
0
Order By: Relevance
“…Historically many restrictions to the practical model of teaching food microbiology in the public school have been cited by primary school teachers, including limited budgets, poor access to resources and inability to do experimental work with microorganisms (Egan et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically many restrictions to the practical model of teaching food microbiology in the public school have been cited by primary school teachers, including limited budgets, poor access to resources and inability to do experimental work with microorganisms (Egan et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Food safety education of children is thought to be essential for the development of proper handling of food practices (Haapala and Probert, 2004;Youatt et al, 1996); moreover, teaching food hygiene in schools could be an effective way to reach all the family members, as students share knowledge on correct practices in the home setting (Egan et al, 2008;Haapala and Probert, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Eves et al 22 found that students between 4 and 14 years of age had good awareness of food hygiene-related issues but had misperceptions about microorganisms and their effects on foods. In other research in which food safety education in secondary schools was studied, it was stated that the best education method was the demonstration method, and that shortages of materials and short class time periods posed serious obstacles 24 . These findings show that those in power need to take action to increase the knowledge and awareness level of students, and consequently of the community, in terms of curriculum and classroom materials.…”
Section: Resultsmentioning
confidence: 99%
“…Despite numerous researches carried out on food services and canteens in the foreign literature [16][17][18][19] , Turkey is experiencing difficulties in identifying studies in sufficient numbers which were carried out in dining halls in Turkey 20 . Behaviours, knowledge of and attitudes to food safety in kindergartens/nursery schools, school and university canteens, and their personnel, teachers and/or students were assessed independently of each other [21][22][23][24][25][26] . On the other hand, this study, aiming to assess the relationship between the level of knowledge on and attitude to food safety, and to determine the effect of knowledge on attitude, should contribute to the existing literature.…”
mentioning
confidence: 99%
“…No standard methodology currently exists for the integration of food hygiene and safety into school curricula (Caraher, Wu, & Seeley, 2010;Egan et al, 2008). However, in the field of hygiene, infection prevention and antibiotic resistance, free educational resources are provided by e-Bug (www.e-bug.eu).…”
Section: Classroom-based Interventionsmentioning
confidence: 99%